Non-Communicable Diseases and Health Indices of Adolescents in Jamaica: A National Perspective (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: adolescents; cardiovasuclar diseases; chronic condition; developing nations; health; jamaica; lifestyle practices; non-communicable diseases